A Data Envelopment Analysis Approach to Assess Technical Efficiency of Large and Medium Manufacturing Industry in Central Java Province, Indonesia - M. Mujiya Ulkhaq; Trisna Nagris Pratiwi (International Economic and Finance Review, 2022)
Technical efficiency of Indonesian manufacturing industry has been measured in several studies. However, there is limited study conducted in large and medium manufacturing industries context. This study, therefore, aims to analyse the technical efficiency of the large and medium manufacturing industries in Central Java Province, Indonesia. Understanding the technical efficiency is important as firms with full technical efficiency, the less inputs they use, the larger output they achieve. Data envelopment analysis with output-oriented and variable returns-to-scale is used to accomplish the objective of this study. The output is measured by total output value, while the inputs are cost of labour, raw materials, other materials, fuel, electricity, and fixed capital. Result shows that among twenty-four decision-making units under-investigated, six of them are considered as the most efficient. Keywords: Central Java Province, data envelopment analysis, Indonesia, industry, large and medium manufacturing